Integrative Thematic Module with Ethnopedagogic-Based Blended Learning Model in Grade 1 Elementary School - Satria, Tio Gusti; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The development of the 2013 curriculum with integrative thematic learning carries literacy in achieving learning success. In addition, the use of teaching materials with ethnopedagogic concepts contained in each basic competency in the subject is intended to make learning meaningful. Its implementation is difficult considering the low literacy rate that students have and teaching materials are relevant to current learning conditions that demand the use of blended learning as a result of the pandemic. Research to develop teaching material products in the form of modules with the Ethnopedagogic-Based Blended Learning model. This type of research is Research and Development (R & D) using the Dick and Carrey model. data collection techniques were carried out through interviews and questionnaires. The data analysis technique uses the percentage value of the score obtained. The results showed that: 1) The module in terms of validity was categorized as valid with a percentage score of 88%; 2) Modules seen from practicality are categorized as practical, individual student responses with a percentage of 89% while small group student responses with a percentage of 87%. It can be concluded that the Integrative Thematic module with the Ethnopedagogic-Based Blended Learning model in Grade 1 SD semester 1 meets the valid and practical criteria and can be used in learning.